#### Answer

7

#### Work Step by Step

$(4y+3z^2)$ $\longrightarrow$ substitute
=$4(-5)+3(3)^2$ $\longrightarrow$ solve exponent
=$4(-5)+3(9)$ $\longrightarrow$ multiply
=$-20+27$ $\longrightarrow$ add
=$7$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

7

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.